A morphology-controllable Cu-Co composite metal catalyst and its preparation method and application

By controlling the hydrothermal reaction temperature and the composition of roasted materials, the morphology of Cu-Co composite metal catalyst is solved, and the problem of difficult catalyst morphology regulation in the prior art is improved, the catalytic activity and anti-CO poisoning ability are extended, and the service life is achieved is achieved, and the catalyst is efficient, environmentally friendly and economical.

CN119746860APending Publication Date: 2025-04-04YANTAI ADVANCED MATERIALS & GREEN MFG SHANDONG PROVINCIAL LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411448345.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively regulate the morphology of the catalyst, resulting in insufficient catalytic activity and anti-CO poisoning ability, and poor thermal stability of the catalyst, affecting its service life.

Method used

By controlling the temperature of the hydrothermal reaction and the composition of the roasted material, the morphology of Cu-Co composite metal catalyst can be controlled, including sea urchin-like, petal-like and sheet-like morphology.

Benefits of technology

It improves the catalytic activity and anti-CO poisoning ability of the catalyst, extends the service life of the catalyst, and the catalyst has good thermal stability and environmental friendliness, and is easy to reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746860A_ABST
    Figure CN119746860A_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of catalytic materials, and provides a morphology-controllable Cu-Co composite metal catalyst and its preparation method and application. The present invention adds a nitrogen-containing compound solution to a metal salt solution, performs a hydrothermal reaction, and obtains a catalyst precursor; the calcined material is calcined to obtain. The present invention can adjust the morphology of the final Cu-Co composite metal catalyst by controlling the temperature of the hydrothermal reaction and the composition of the calcined material, specifically: the temperature of the hydrothermal reaction is greater than or equal to 100°C, and less than or equal to 120°C, and the catalyst is sea urchin-shaped; the temperature of the hydrothermal reaction is greater than 120°C, and less than or equal to 160°C, and the catalyst is petal-shaped; when the temperature of the hydrothermal reaction is greater than 160°C and less than or equal to 200°C, the catalyst is flaky; when the temperature of the hydrothermal reaction is 100-200°C, and the calcined material is a catalyst precursor-cerium compound mixture, the morphology of the obtained catalyst is flaky.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalytic technology, and in particular to a morphology-controllable Cu-Co composite metal catalyst and a preparation method and application thereof. Background Art

[0002] As an important clean energy, hydrogen has attracted widespread attention due to its advantages such as high calorific value, wide sources, and green and pollution-free. The natural gas cracking hydrogen production process is simple, low-cost, and high in conversion efficiency, and occupies an important position in many hydrogen production processes. However, in addition to the necessary hydrogen, the natural gas cracking products also contain a small amount of toxic gases, such as CO. CO will not only cause catalyst poisoning, resulting in reduced production efficiency; excessive CO will also combine with hemoglobin, causing hypoxia in the human body, damaging body functions, and even causing death. In view of the serious hazards of CO, it is particularly necessary to remove CO during the hydrogen purification process.

[0003] The methods for removing CO mainly include adsorption, combustion and catalytic oxidation. Among them, catalytic oxidation has high catalytic activity, high stability and high selectivity, and is the most ideal method for CO purification. In terms of catalyst selection, considering the comprehensive effect, cost and environmental factors, transition metal catalysts have greater potential in industrial production. The relevant prior art discloses a doped non-precious metal compound as a CO oxidation catalyst and a preparation method. The patent obtains a series of doped non-precious metal compound catalysts by changing the synthesis conditions such as the type of transition metal salt, the ratio of transition metal salt to cerium salt, and the heat treatment temperature. 2 Compared with the catalyst, the catalytic activity of the obtained catalyst for CO oxidation is greatly improved. However, the catalysts prepared by atomization fusion are all spherical, and the crystal morphology cannot be controlled. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a morphology-controllable Cu-Co composite metal catalyst and its preparation method and application. The method of the present invention can achieve morphology control of the obtained Cu-Co composite metal catalyst, and the control method is easy to operate.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a morphology-controllable Cu-Co composite metal catalyst, comprising the following steps:

[0007] Dissolving copper salt and cobalt salt in an organic solvent to obtain a metal salt solution;

[0008] dissolving the nitrogen-containing compound in an organic solvent to obtain a nitrogen-containing compound solution;

[0009] adding the nitrogen-containing compound solution to the metal salt solution to carry out a hydrothermal reaction to obtain a catalyst precursor;

[0010] calcining the calcined material to obtain the Cu-Co composite metal catalyst;

[0011] The calcined material is a catalyst precursor or a catalyst precursor-cerium compound mixture;

[0012] The temperature of the hydrothermal reaction is 100-200°C;

[0013] The temperature of the hydrothermal reaction is greater than or equal to 100° C. and less than or equal to 120° C., and when the calcined material is a catalyst precursor, the Cu-Co composite metal catalyst has a sea urchin-like morphology;

[0014] The temperature of the hydrothermal reaction is greater than 120° C. and less than or equal to 160° C., and when the calcined material is a catalyst precursor, the morphology of the Cu-Co composite metal catalyst is petal-shaped;

[0015] When the temperature of the hydrothermal reaction is greater than 160° C. and less than or equal to 200° C., and when the calcined material is a catalyst precursor, the Cu-Co composite metal catalyst has a flaky morphology;

[0016] When the temperature of the hydrothermal reaction is 100-200° C. and the calcined material is a catalyst precursor-cerium compound mixture, the Cu-Co composite metal catalyst has a flaky morphology; and the mass ratio of the catalyst precursor to the cerium compound in the catalyst precursor-cerium compound mixture is 1:0.3-1, calculated as oxides.

[0017] Preferably, the copper salt includes one or more of copper nitrate, copper sulfate, copper chloride and copper acetate, the cobalt salt includes one or more of cobalt nitrate, cobalt sulfate, cobalt chloride and cobalt acetate, the organic solvent includes one or more of N,N-dimethylamide, methanol, ethanol and acetone, and the nitrogen-containing compound includes one or more of ammonium chloride, ammonium carbonate, ammonium bicarbonate and urea.

[0018] Preferably, the copper salt is calculated as copper oxide, the cobalt salt is calculated as cobalt oxide, and the mass ratio of the copper salt to the cobalt salt is 1 to 5:1; in the metal salt solution, the total mass of the copper salt and the cobalt salt and the amount of the organic solvent are 0.05 to 0.2 g / mL;

[0019] In the nitrogen-containing compound solution, the mass ratio of the nitrogen-containing compound to the organic solvent is 0.01-0.05:1.

[0020] Preferably, the volume ratio of the metal salt solution to the nitrogen-containing compound solution is 1:0.2-1.

[0021] Preferably, the nitrogen-containing compound solution is added dropwise at a rate of 0.5 to 2 mL / min;

[0022] After the nitrogen-containing compound solution is added, constant temperature stirring and ultrasound are sequentially performed, wherein the constant temperature stirring temperature is 30 to 50° C. and the time is 2 to 6 hours;

[0023] The power of the ultrasound is 50-100KW, the frequency is 40-80KHz, and the time is 0.5-5h.

[0024] Preferably, the hydrothermal reaction time is 6 to 24 hours.

[0025] Preferably, after the hydrothermal reaction, the process further comprises: washing and drying the obtained solid in sequence to obtain the catalyst precursor, wherein the drying temperature is 60 to 150° C. and the drying time is 12 to 24 hours.

[0026] Preferably, the calcination is carried out in a reducing atmosphere, the reducing atmosphere comprises a reducing gas and a balance gas, the volume concentration of the reducing gas in the reducing atmosphere is 10% to 50%, and the reducing gas comprises H 2 , CO or NO; the air flow rate of the reducing atmosphere is 100 to 200 mL / min;

[0027] The calcination temperature is 500-800° C., the rate of heating to the calcination temperature is 1-5° C. / min, and the heat preservation time is 2-5 hours.

[0028] The present invention also provides a Cu-Co composite metal catalyst obtained by the preparation method described in the above technical solution.

[0029] The present invention also provides the use of the Cu-Co composite metal catalyst described in the above technical solution in photoelectrocatalysis or CO purification.

[0030] The invention provides a method for preparing a Cu-Co composite metal catalyst with controllable morphology.

[0031] The present invention can adjust the morphology of the finally obtained Cu-Co composite metal catalyst by controlling the temperature of the hydrothermal reaction and the composition of the calcined material, specifically: when the temperature of the hydrothermal reaction is greater than or equal to 100°C and less than or equal to 120°C, and the calcined material is a catalyst precursor, the morphology of the obtained catalyst is sea urchin-shaped; when the temperature of the hydrothermal reaction is greater than 120°C and less than or equal to 160°C, and the calcined material is a catalyst precursor, the morphology of the obtained catalyst is petal-shaped; when the temperature of the hydrothermal reaction is greater than 160°C and less than or equal to 200°C, and the calcined material is a catalyst precursor, the morphology of the Cu-Co composite metal catalyst is flaky; when the temperature of the hydrothermal reaction is 100-200°C, and the calcined material is a catalyst precursor-cerium compound mixture, the morphology of the obtained catalyst is flaky. The Cu-Co composite metal catalyst obtained by the present invention has an excellent catalyst structure and improves catalytic activity; in addition, it also has good CO poisoning resistance and thermal stability, effectively prolongs the service life of the catalyst, and provides more possibilities for the application of the catalyst in actual production. Compared with existing catalysts, the present invention is green and economical, and the catalyst is easy to reuse. While solving the CO pollution problem, it responds to the national call for energy conservation and consumption reduction, and has good environmental and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is the conversion rate of CO by different catalysts;

[0033] Figure 2 is the selectivity of different catalysts to CO;

[0034] Figure 3 The scanning electron microscope photographs of the catalysts obtained in Examples 1 to 6;

[0035] Figure 4 The XRD patterns of the catalysts obtained in Examples 1 to 6 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0036] The present invention provides a method for preparing a morphology-controllable Cu-Co composite metal catalyst, comprising the following steps:

[0037] Dissolving copper salt and cobalt salt in an organic solvent to obtain a metal salt solution;

[0038] dissolving the nitrogen-containing compound in an organic solvent to obtain a nitrogen-containing compound solution;

[0039] adding the nitrogen-containing compound solution to the metal salt solution to carry out a hydrothermal reaction to obtain a catalyst precursor;

[0040] calcining the calcined material to obtain the Cu-Co composite metal catalyst;

[0041] The calcined material is a catalyst precursor or a catalyst precursor-cerium compound mixture;

[0042] The temperature of the hydrothermal reaction is 100-200°C;

[0043] The temperature of the hydrothermal reaction is greater than or equal to 100° C. and less than or equal to 120° C., and when the calcined material is a catalyst precursor, the Cu-Co composite metal catalyst has a sea urchin-like morphology;

[0044] The temperature of the hydrothermal reaction is greater than 120° C. and less than or equal to 160° C., and when the calcined material is a catalyst precursor, the morphology of the Cu-Co composite metal catalyst is petal-shaped;

[0045] When the temperature of the hydrothermal reaction is greater than 160° C. and less than or equal to 200° C., and when the calcined material is a catalyst precursor, the Cu-Co composite metal catalyst has a flaky morphology;

[0046] When the temperature of the hydrothermal reaction is 100-200° C. and the calcined material is a catalyst precursor-cerium compound mixture, the Cu-Co composite metal catalyst has a flaky morphology; and the mass ratio of the catalyst precursor to the cerium compound in the catalyst precursor-cerium compound mixture is 1:0.3-1, calculated as oxides.

[0047] In the present invention, unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.

[0048] The invention dissolves copper salt and cobalt salt in an organic solvent to obtain a metal salt solution.

[0049] In the present invention, the copper salt preferably includes one or more of copper nitrate, copper sulfate, copper chloride and copper acetate. In the present invention, the cobalt salt preferably includes one or more of cobalt nitrate, cobalt sulfate, cobalt chloride and cobalt acetate. In the present invention, the organic solvent preferably includes one or more of N,N-dimethylamide (DMF), methanol, ethanol and acetone. In the present invention, the copper salt is calculated as copper oxide, the cobalt salt is calculated as cobalt oxide, and the mass ratio of the copper salt to the cobalt salt is preferably 1 to 5:1, specifically 1:1, 2:1, 3:1, 4:1 or 5:1; in the metal salt solution, the total mass of the copper salt and the cobalt salt and the amount of the organic solvent are preferably 0.05 to 0.2 g / mL, specifically 0.05 g / mL, 0.1 g / mL, 0.15 g / mL or 0.2 g / mL.

[0050] The present invention dissolves the nitrogen-containing compound in an organic solvent to obtain a nitrogen-containing compound solution.

[0051] In the present invention, the nitrogen-containing compound preferably includes one or more of ammonium chloride, ammonium carbonate, ammonium bicarbonate and urea. In the present invention, the type of the organic solvent is preferably consistent with the above technical solution, which is not repeated here. In the present invention, in the nitrogen-containing compound solution, the mass ratio of the nitrogen-containing compound to the organic solvent is preferably 0.01 to 0.05:1, specifically 0.01:1, 0.02:1, 0.03:1, 0.04:1 or 0.05:1.

[0052] After obtaining the metal salt solution and the nitrogen-containing compound solution, the present invention adds the nitrogen-containing compound solution into the metal salt solution to carry out a hydrothermal reaction to obtain a catalyst precursor.

[0053] In the present invention, the volume ratio of the metal salt solution to the nitrogen-containing compound solution is preferably 1:0.2-1, specifically 1:0.2, 1:0.4, 1:0.5, 1:0.6, 1:0.8 or 1:1.

[0054] In the present invention, the nitrogen-containing compound solution is preferably added dropwise, and the dropping speed is preferably 0.5-2 mL / min, specifically 0.5 mL / min, 0.8 mL / min, 1 mL / min, 1.5 mL / min or 2 mL / min.

[0055] After the nitrogen-containing compound solution is added, the present invention preferably further comprises constant temperature stirring and ultrasound in sequence. In the present invention, the temperature of the constant temperature stirring is preferably 30-50°C, specifically 30°C, 35°C, 40°C, 45°C or 50°C; the time is preferably 2-6h, specifically 2h, 3h, 4h, 5h or 6h. In the present invention, the power of the ultrasound is preferably 50-100KW, specifically 50KW, 60KW, 70KW, 80KW, 90KW or 100KW; the frequency is preferably 40-80KHz, specifically 40KHz, 50KHz, 60KHz, 70KHz or 80KHz; the time is preferably 0.5-5h, specifically 0.5h, 1h, 1.5h, 2h, 3h, 4h or 5h. In the present invention, ultrasound has two functions: 1. Fully mix the mixed solution to evenly disperse the metal atoms in the solution; 2. Ultrasonic energy stimulation stimulates the oscillation of the electrons outside the nuclei of metal atoms, making them more active, strengthening the interaction between atoms, and making it easier to generate metal complexes.

[0056] In the present invention, the temperature of the hydrothermal reaction is 100-200°C, and the time is preferably 6-24 hours. In the present invention, the hydrothermal reaction is preferably carried out in a high-temperature reactor.

[0057] After the hydrothermal reaction, the present invention preferably further comprises: washing and drying the obtained solid in sequence to obtain the catalyst precursor. In the present invention, the drying temperature is preferably 60 to 150°C, specifically 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C; the drying time is preferably 12 to 24 hours, specifically 12 hours, 16 hours, 20 hours or 24 hours.

[0058] In the present invention, during the hydrothermal reaction, the nitrogen-containing compound will decompose ammonia, and the uniformly dispersed nitrogen-containing compound will construct the pores of the catalyst through the overflowing tiny ammonia bubbles, and the attached ammonia molecules will combine with the surface metal to change the surface acidity and alkalinity of the catalyst. The nitrogen-containing compound solution is added dropwise mainly to avoid the problem of agglomeration of metal atoms during the transfer during the mixing process.

[0059] After obtaining the catalyst precursor, the present invention calcines the calcined material to obtain the Cu-Co composite metal catalyst; the calcined material is the catalyst precursor or a catalyst precursor-cerium compound mixture.

[0060] In the present invention, the calcination is preferably carried out under a reducing atmosphere, the reducing atmosphere preferably comprises a reducing gas and a balance gas, the volume concentration of the reducing gas in the reducing atmosphere is preferably 10% to 50%, specifically 10%, 20%, 30%, 40% or 50%, and the reducing gas preferably comprises H 2 , CO or NO; the balance gas is preferably nitrogen; the air intake flow rate of the reducing atmosphere is preferably 100-200mL / min, specifically 100mL / min, 120mL / min, 140mL / min, 150mL / min, 160mL / min, 180mL / min or 200mL / min.

[0061] In the present invention, the calcination temperature is preferably 500-800°C, specifically 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C; the rate of heating to the calcination temperature is preferably 1-5°C / min, specifically 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, and the holding time is preferably 2-5h, specifically 2h, 3h, 4h or 5h. In the present invention, the calcination is preferably carried out in a tubular furnace.

[0062] In the present invention, the temperature of the hydrothermal reaction is greater than or equal to 100° C. and less than or equal to 120° C., and when the calcined material is a catalyst precursor, the morphology of the Cu-Co composite metal catalyst is sea urchin-like.

[0063] In the present invention, the temperature of the hydrothermal reaction is greater than 120° C. and less than or equal to 160° C., and when the calcined material is a catalyst precursor, the morphology of the Cu-Co composite metal catalyst is petal-shaped.

[0064] In the present invention, when the temperature of the hydrothermal reaction is greater than 160° C. and less than or equal to 200° C., and when the calcined material is a catalyst precursor, the Cu-Co composite metal catalyst has a flaky morphology.

[0065] In the present invention, when the temperature of the hydrothermal reaction is 100-200°C and the calcined material is a catalyst precursor-cerium compound mixture, the morphology of the Cu-Co composite metal catalyst is flaky; in terms of oxide, the mass ratio of the catalyst precursor and the cerium compound in the catalyst precursor-cerium compound mixture is 1:0.3-1, and is preferably 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1. In the present invention, the cerium compound preferably includes one or more of cerium nitrate, cerium sulfate, cerium chloride and cerium acetate. In the present invention, the cerium compound mainly forms a synergistic effect with the catalyst precursor through a heterojunction to form a Ce-doped Cu-Co composite metal catalyst, that is, different and different exposed crystal faces, change the growth mode of the crystal, accelerate the conversion to a stable structure, and thus achieve fine-tuning of the structure. In addition, under high temperature conditions, cerium will penetrate into the skeleton of the composite metal, causing the structure of the catalyst to change.

[0066] The present invention also provides a Cu-Co composite metal catalyst obtained by the preparation method described in the above technical solution.

[0067] The present invention also provides the use of the Cu-Co composite metal catalyst described in the above technical solution in photoelectrocatalysis or CO purification.

[0068] The present invention does not specifically limit the application method of the Cu-Co composite metal catalyst, and the application method familiar to those skilled in the art can be used.

[0069] The morphology-controllable Cu-Co composite metal catalyst provided by the present invention, its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0070] Example 1

[0071] A method for preparing a Cu-Co composite metal catalyst specifically comprises the following steps:

[0072] (1) According to CuO:Co 3 O 4=1:1, copper nitrate and cobalt nitrate are added to DMF at a ratio of 0.05 g / mL of the total mass of the metal salt to the amount of the organic solvent, and stirred continuously until the metal salt is completely dissolved to obtain a metal salt solution. Ammonium chloride is added to DMF at a mass ratio of 0.01:1 of ammonium chloride to the organic solvent DMF, and stirred continuously until the solid is completely dissolved to obtain an ammonium chloride solution.

[0073] (2) The ammonium chloride solution was added to the metal salt solution at a rate of 0.5 mL / min and stirred at a constant temperature of 30°C for 2 h. After the mixture was uniformly mixed, the mixed solution was ultrasonicated at 50 kW and 40 kHz for 0.5 h to uniformly disperse the metal species in the liquid phase.

[0074] (3) The treated solution is transferred to a high temperature reactor and subjected to a hydrothermal reaction at 120° C. for 6 h to promote the growth of the metal complex. The solid after the reaction is repeatedly filtered and washed, and then dried at 60° C. for 12 h to obtain a catalyst precursor.

[0075] (4) The synthesized catalyst precursor was placed in a tube furnace and 10% H 2 (nitrogen balance), and then heated to 500°C at 1°C / min in a reducing atmosphere and kept at this temperature for 2h to obtain a Cu-Co composite metal catalyst, namely CuCo 2 O 4 -120.

[0076] Example 1-1

[0077] The difference from Example 1 is that the temperature of the hydrothermal reaction is 100° C., and the other aspects are the same as Example 1. The morphology of the obtained composite metal catalyst is sea urchin-like, and the spines are small and short.

[0078] Example 1-2

[0079] The difference from Example 1 is that the temperature of the hydrothermal reaction is 110° C., and the other aspects are the same as Example 1. The morphology of the obtained composite metal catalyst is sea urchin-like, and the spines are longer and thicker than those in Example 1-1.

[0080] Examples 1-3

[0081] The difference from Example 1 is that the temperature of the hydrothermal reaction is 160° C., and the other aspects are the same as Example 1. The morphology of the obtained composite metal catalyst is petal-shaped, and the petals are thick and tightly connected.

[0082] Examples 1-4

[0083] The difference from Example 1 is that the temperature of the hydrothermal reaction is 180° C., and the other aspects are the same as Example 1. The morphology of the obtained composite metal catalyst is a light thin plate layer with a small amount of petal-like features with clear texture.

[0084] Examples 1-5

[0085] The difference from Example 1 is that the temperature of the hydrothermal reaction is 200° C., and the other aspects are the same as Example 1. The morphology of the obtained composite metal catalyst is thick plate-like, and the arrangement between the plates is relatively regular.

[0086] Example 2

[0087] (1) According to CuO:Co 3 O 4 =2:1, the total mass of metal salt to organic solvent ratio is 0.08g / mL, copper nitrate, copper chloride and cobalt chloride are added to methanol, wherein the mass ratio of copper nitrate to copper chloride is 2:1, and stirring is continued until the metal salt is completely dissolved, that is, a metal salt solution. Ammonium carbonate is added to methanol at a mass ratio of ammonium carbonate to organic solvent methanol of 0.02:1, and stirring is continued until the solid is completely dissolved, that is, an ammonium carbonate solution.

[0088] (2) The ammonium carbonate solution was added to the metal salt solution at a rate of 0.8 mL / min and stirred at 35°C for 3 h. After the mixture was uniformly mixed, the mixed solution was ultrasonicated at 60 kW and 50 kHz for 1 h to uniformly disperse the metal species in the liquid phase.

[0089] (3) The treated solution is transferred to a high temperature reactor and subjected to a hydrothermal reaction at 160° C. for 12 h to promote the growth of the metal complex. The solid after the reaction is repeatedly filtered and washed, and then dried at 80° C. for 15 h to obtain a catalyst precursor.

[0090] (4) The synthesized catalyst precursor was placed in a tube furnace, 20% CO (nitrogen balance) was injected at a flow rate of 120 mL / min, and the temperature was raised to 600°C at 2°C / min under a reducing atmosphere and kept constant for 3 h to obtain a Cu-Co composite metal catalyst, namely CuCo 2 O 4 -160.

[0091] Example 2-1

[0092] The difference from Example 2 is that the temperature of the hydrothermal reaction is 100° C., and the other aspects are the same as Example 2. The morphology of the obtained composite metal catalyst is sea urchin-like, and the spines are relatively small and short.

[0093] Example 2-2

[0094] The difference from Example 2 is that the temperature of the hydrothermal reaction is 110° C., and the other aspects are the same as Example 2. The morphology of the obtained composite metal catalyst is sea urchin-like, and the spines are longer and thicker than those in Example 2-1.

[0095] Example 2-3

[0096] The difference from Example 2 is that the temperature of the hydrothermal reaction is 120° C., and the other aspects are the same as Example 2. The morphology of the obtained composite metal catalyst is sea urchin-like, and the spines are longer and thicker than those in 2-2.

[0097] Embodiment 2-4

[0098] The difference from Example 2 is that the temperature of the hydrothermal reaction is 180° C., and the other aspects are the same as Example 2. The morphology of the obtained composite metal catalyst is a light thin plate layer with a small amount of petal-like features with clear texture.

[0099] Embodiment 2-5

[0100] The difference from Example 2 is that the temperature of the hydrothermal reaction is 200° C., and the other aspects are the same as Example 2. The morphology of the obtained composite metal catalyst is thick plate-like, and the arrangement between the plates is relatively regular.

[0101] Example 3

[0102] (1) According to CuO:Co 3 O 4 =3:1, the total mass of the metal salt and the amount of the organic solvent are 0.1g / mL. Copper sulfate, copper acetate and cobalt acetate are added to ethanol, wherein the mass ratio of copper sulfate to copper acetate is 2:1, and stirring is continued until the metal salt is completely dissolved, that is, a metal salt solution. Ammonium bicarbonate is added to ethanol at a mass ratio of ammonium bicarbonate to the organic solvent ethanol of 0.03:1, and stirring is continued until the solid is completely dissolved, that is, an ammonium bicarbonate solution.

[0103] (2) The ammonium bicarbonate solution was added to the metal salt solution at a rate of 1 mL / min and stirred at a constant temperature of 40°C for 4 h. After the mixture was uniformly mixed, the mixed solution was ultrasonicated at 70 kW and 60 kHz for 2 h to uniformly disperse the metal species in the liquid phase.

[0104] (3) The treated solution is transferred to a high temperature reactor and subjected to a hydrothermal reaction at 200° C. for 15 h to promote the growth of the metal complex. The solid after the reaction is repeatedly filtered and washed, and then dried at 100° C. for 18 h to obtain a catalyst precursor.

[0105] (4) The synthesized catalyst precursor was placed in a tube furnace, 30% NO (nitrogen balance) was injected at a flow rate of 150 mL / min, and the temperature was raised to 700°C at 3°C / min under a reducing atmosphere and kept constant for 4 h to obtain a Cu-Co composite metal catalyst, namely CuCo 2 O 4 -200.

[0106] Example 3-1

[0107] The difference from Example 3 is that the temperature of the hydrothermal reaction is 100° C., and the other aspects are the same as Example 3. The morphology of the obtained composite metal catalyst is sea urchin-like, and the spines are relatively small and short.

[0108] Example 3-2

[0109] The difference from Example 3 is that the temperature of the hydrothermal reaction is 110° C., and the other aspects are the same as Example 3. The morphology of the obtained composite metal catalyst is sea urchin-like, and the spines are longer and thicker than those in Example 3-1.

[0110] Example 3-3

[0111] The difference from Example 3 is that the temperature of the hydrothermal reaction is 120° C., and the other aspects are the same as Example 3. The morphology of the obtained composite metal catalyst is sea urchin-like, and the spines are longer and thicker than those of 3-2.

[0112] Embodiment 3-4

[0113] The difference from Example 3 is that the temperature of the hydrothermal reaction is 160° C., and the other conditions are the same as Example 3. The morphology of the obtained composite metal catalyst is petal-shaped, and the overall distribution of the petals is relatively scattered.

[0114] Embodiment 3-5

[0115] The difference from Example 3 is that the temperature of the hydrothermal reaction is 180° C., and the other conditions are the same as Example 3. The morphology of the obtained composite metal catalyst is a light and thin plate layer, and a small amount of petal-like structures of different morphologies are distributed between the plate layers.

[0116] Example 4

[0117] (1) According to CuO:Co 3 O 4 =4:1, the total mass of metal salt to organic solvent ratio is 0.15g / mL, copper nitrate, copper chloride, copper sulfate, cobalt chloride and cobalt sulfate are added to acetone, wherein the mass ratio of copper nitrate, copper chloride and copper sulfate is 5:1:1; the mass ratio of cobalt chloride and cobalt sulfate is 1:5; stirring is continued until the metal salt is completely dissolved, that is, the metal salt solution. Urea is added to acetone at a mass ratio of 0.04:1 of urea to the organic solvent acetone, and stirring is continued until the solid is completely dissolved, that is, the urea solution.

[0118] (2) The urea solution was added to the metal salt solution at a rate of 1.5 mL / min and stirred at a constant temperature of 45°C for 5 h. After the mixture was uniformly mixed, the mixed solution was ultrasonicated at 80 kW and 70 kHz for 3 h to uniformly disperse the metal species in the liquid phase.

[0119] (3) The treated solution is transferred to a high temperature reactor and subjected to a hydrothermal reaction at 120° C. for 18 h to promote the growth of the metal complex. The solid after the reaction is repeatedly filtered and washed, and then dried at 120° C. for 20 h to obtain a catalyst precursor.

[0120] (4) Cerium nitrate (CeO 2 After the mixture is mixed with the catalyst precursor at a mass ratio of 0.3:1, the mixed solid is placed in a tube furnace, 40% CO (nitrogen balance) is injected at a flow rate of 180 mL / min, and the temperature is raised to 800°C at a rate of 4°C / min under a reducing atmosphere and kept at a constant temperature for 5 hours to obtain a Cu-Co composite metal catalyst, namely Ce 0.3 / CuCo 2 O 4 -120.

[0121] Example 4-1

[0122] The difference from Example 4 is that the temperature of the hydrothermal reaction is 100° C., and the other aspects are the same as Example 4. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is extremely thin and porous, and the arrangement between the layers is disordered.

[0123] Example 4-2

[0124] The difference from Example 4 is that the temperature of the hydrothermal reaction is 110°C, and the rest is the same as Example 4. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is thicker and more porous than 4-1, and the arrangement between the layers is disordered.

[0125] Example 4-3

[0126] The difference from Example 4 is that the temperature of the hydrothermal reaction is 160°C, and the other aspects are the same as Example 4. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is thicker and more porous than 4-2, and the interlayer arrangement is more regular.

[0127] Example 4-4

[0128] The difference from Example 4 is that the temperature of the hydrothermal reaction is 180°C, and the other aspects are the same as Example 4. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is thicker and more porous than 4-3, and the interlayer arrangement is more regular.

[0129] Embodiment 4-5

[0130] The difference from Example 4 is that the temperature of the hydrothermal reaction is 200° C., and the other aspects are the same as Example 4. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is thick and porous, and the arrangement between layers is relatively regular.

[0131] Example 5

[0132] (1) According to CuO:Co 3O 4 =5:1, the total mass of the metal salt and the amount of the organic solvent are 0.18g / mL. Copper chloride, copper sulfate, copper acetate, cobalt nitrate and cobalt acetate are added to DMF, wherein the mass ratio of copper chloride, copper sulfate and copper acetate is 1:2:1, and the mass ratio of cobalt nitrate and cobalt acetate is 1:1, and stirring is continued until the metal salt is completely dissolved, that is, a metal salt solution. Ammonium bicarbonate is added to DMF at a mass ratio of ammonium bicarbonate to the organic solvent DMF of 0.05:1, and stirring is continued until the solid is completely dissolved, that is, an ammonium bicarbonate solution.

[0133] (2) The ammonium bicarbonate solution was added to the metal salt solution at a rate of 1.8 mL / min and stirred at a constant temperature of 50° C. for 6 h. After being evenly mixed, the mixed solution was ultrasonicated at 90 kW and 80 kHz for 4 h to uniformly disperse the metal species in the liquid phase.

[0134] (3) The treated solution is transferred to a high temperature reactor and subjected to a hydrothermal reaction at 160° C. for 20 h to promote the growth of the metal complex. The solid after the reaction is repeatedly filtered and washed, and then dried at 150° C. for 24 h to obtain a catalyst precursor.

[0135] (4) The cerium compound (CeO 2 The cerium compound includes cerium nitrate and cerium chloride, and the mass ratio of the two is 1:1) and the catalyst precursor is mixed in a mass ratio of 0.3:1, the mixed solid is placed in a tube furnace, 50% NO (nitrogen balance) is injected at a flow rate of 200 mL / min, and the temperature is raised to 800 at a rate of 5°C / min under a reducing atmosphere and kept at a constant temperature for 2h to obtain a Cu-Co composite metal catalyst, namely Ce 0.3 / CuCo 2 O 4 -160.

[0136] Example 5-1

[0137] The difference from Example 5 is that the temperature of the hydrothermal reaction is 100° C., and the other aspects are the same as Example 5. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is extremely thin and porous, and the arrangement between the layers is disordered.

[0138] Example 5-2

[0139] The difference from Example 5 is that the temperature of the hydrothermal reaction is 110°C, and the other aspects are the same as Example 5. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is thicker and more porous than 5-1, and the arrangement between the layers is disordered.

[0140] Example 5-3

[0141] The difference from Example 5 is that the temperature of the hydrothermal reaction is 120°C, and the other conditions are the same as Example 5. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is thicker and more porous than 5-2, and the arrangement between the layers is disordered.

[0142] Example 5-4

[0143] The difference from Example 5 is that the temperature of the hydrothermal reaction is 180°C, and the other aspects are the same as Example 5. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is thicker and more porous than 5-3, and the arrangement between layers is slightly disordered.

[0144] Example 5-5

[0145] The difference from Example 5 is that the temperature of the hydrothermal reaction is 200°C, and the other conditions are the same as Example 5. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is thicker and more porous than 5-4, and the arrangement between the layers is slightly disordered.

[0146] Example 6

[0147] (1) According to CuO:Co 3 O 4 =5:1, the total mass of the metal salt and the amount of the organic solvent methanol are in a ratio of 0.2g / mL. Copper nitrate, copper sulfate, copper chloride, copper acetate, cobalt nitrate, cobalt chloride and cobalt sulfate are added to methanol, wherein the mass ratio of copper nitrate, copper sulfate, copper chloride and copper acetate is 5:2:1:1, and the mass ratio of cobalt nitrate, cobalt chloride and cobalt sulfate is 2:1:2. Stir continuously until the metal salt is completely dissolved to obtain a metal salt solution. Urea is added to methanol at a mass ratio of 0.05:1 of urea to methanol, and stirred continuously until the solid is completely dissolved to obtain a urea solution.

[0148] (2) The urea solution was added to the metal salt solution at a rate of 2 mL / min and stirred at a constant temperature of 30°C for 6 h. After the mixture was uniformly mixed, the mixed solution was ultrasonicated at 100 kW and 80 kHz for 5 h to uniformly disperse the metal species in the liquid phase.

[0149] (3) The treated solution is transferred to a high temperature reactor and subjected to a hydrothermal reaction at 200° C. for 24 hours to promote the growth of the metal complex. The solid after the reaction is repeatedly filtered and washed, and then dried at 80° C. for 24 hours to obtain a catalyst precursor.

[0150] (4) The cerium compound (CeO 2 The cerium compound includes cerium nitrate, cerium chloride, cerium sulfate and cerium acetate, and the mass ratio of the four is 5:1:1:1) and the catalyst precursor is mixed at a mass ratio of 0.3:1, and the mixed solid is placed in a tube furnace, and 50% H 2(nitrogen balance), and then heated to 500°C at 2°C / min in a reducing atmosphere and kept at this temperature for 5h to obtain a Cu-Co composite metal catalyst, namely Ce 0.3 / CuCo 2 O 4 -200.

[0151] Example 6-1

[0152] The difference from Example 6 is that the temperature of the hydrothermal reaction is 100° C., and the other aspects are the same as Example 6. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is extremely thin and porous, and the arrangement between the layers is disordered.

[0153] Example 6-2

[0154] The difference from Example 6 is that the temperature of the hydrothermal reaction is 110°C, and the rest is the same as Example 6. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is thicker and more porous than 6-1, and the arrangement between layers is disordered.

[0155] Example 6-3

[0156] The difference from Example 6 is that the temperature of the hydrothermal reaction is 120°C, and the rest is the same as Example 6. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is thicker and more porous than 6-2, and the arrangement between the layers is disordered.

[0157] Example 6-4

[0158] The difference from Example 6 is that the temperature of the hydrothermal reaction is 160°C, and the rest is the same as Example 6. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is thicker and more porous than 6-3, and the arrangement between layers is more regular.

[0159] Example 6-5

[0160] The difference from Example 6 is that the temperature of the hydrothermal reaction is 180°C, and the other aspects are the same as Example 6. The morphology of the obtained composite metal catalyst is lamellar, the surface layer is thicker and more porous than 6-4, and the layers are arranged regularly.

[0161] Comparative Example 1

[0162] The difference from Example 6 is that the catalyst preparation process is directly calcined with cerium salt without oxygen, and the other parameters and steps are the same, that is, the blank control CeO 2 .

[0163] Carbon dioxide conversion and selectivity test:

[0164] The CO concentration is 1%, H 2 The concentration is 50%, and the balance is N 2The atmospheric pressure mixed reaction atmosphere was uniformly passed through the quartz tube at a constant flow rate of 220 mL / min, and reacted with the catalysts obtained in the examples and comparative examples at 30-220°C. The conversion rate was calculated by the change in CO concentration before and after the reaction. 2 The selectivity is calculated by changing the ratio of CO concentration. The results are as follows: Figure 1 , Figure 2 And as shown in Table 1. Figure 1 is the conversion rate of CO over different catalysts, Figure 2 is the selectivity of different catalysts for CO.

[0165] Table 1 Conversion rate and selectivity of the catalysts obtained in the examples and comparative examples

[0166]

[0167]

[0168] from Figure 1 and Figure 2 It can be seen that the catalytic effect of the catalyst is mainly related to the hydrothermal reaction temperature, cerium compound modification and calcination, among which the cerium compound modification and hydrothermal reaction temperature have the greatest influence. Figure 1 It can be seen that the catalyst with cerium compound added after hydrothermal treatment at 200 °C has a better effect on CO conversion under low temperature conditions, and 100% CO removal effect can be achieved at 80 °C. Figure 2 Similar results can be obtained with a wider low temperature window, with the temperature window for 100% CO selectivity being 30-100 °C.

[0169] Figure 3 are scanning electron microscope photos of the catalysts obtained in Examples 1 to 6, wherein a to f are scanning electron microscope photos of the catalysts obtained in Examples 1 to 6, respectively. Figure 3 It can be seen that: a) is sea urchin-shaped, corresponding to a 120°C cerium-free catalyst; b is petal-shaped, corresponding to a medium-temperature cerium-free catalyst; c is lamellar, corresponding to a high-temperature cerium-free catalyst; d~f are lamellar, corresponding to catalysts with different temperatures after adding cerium. From d~f, it can be seen that as the temperature increases, the thickness of the catalyst increases. This shows that at a lower hydrothermal temperature of 100~120°C, the catalyst structure is sea urchin-shaped, and when the temperature is increased to 120~160°C, the catalyst structure is petal-shaped, and continues to heat up to transform into a sheet-shaped structure. With the addition of cerium species, the catalyst maintains a sheet-shaped structure, and the surface of the sheet has a rich pore structure. This shows that hydrothermal temperature and cerium species are important factors in regulating the catalyst structure.

[0170] Figure 4 The XRD patterns of the catalysts obtained in Examples 1 to 6 and Comparative Example 1 are as follows: Figure 4 It can be seen that CuCo 2 O4 CuO is the main component that determines the catalytic activity, among which the structure of the Cu-Co composite metal and the way the crystals are formed are the key factors that determine the morphology of the catalyst.

[0171] In the present invention, the influence of material ratio on morphology is mainly reflected in that different material ratios determine the growth mode of metal crystals. After the component with a large content combines with another component, the remaining material combines around the Cu-Co composite in the form of a complex, and precipitates in the form of metal oxides after roasting. With the continuous accumulation of metal oxides, a variety of morphological structures with the Cu-Co composite as a template will be formed.

[0172] In the present invention, the influence of the hydrothermal reaction temperature is mainly reflected in the regulation of the crystal growth rate and the growth template. The migration of metal ions at low temperatures is slow, and the metal crystals in the morphology composition will grow one by one along a specific direction, while high temperatures will accelerate the transfer of ions, and the crystals will grow rapidly in multiple directions. In addition, high temperatures will cause nitrogen-containing compounds to produce more microbubbles. Changing the edge and surface structure of the catalyst diversifies the growth of the crystal. The role of cerium is to achieve the regulation of the catalyst morphology by coordinating different exposed crystal faces of the metal. In summary: the sea urchin-shaped catalyst condition is low temperature without cerium; the petal-shaped is medium temperature without cerium; the lamellar shape is high temperature without cerium or with the addition of cerium. The influence of the metal salt ratio on the catalyst morphology is mainly carried out by changing the crystal growth mode, that is, the excess metal components will precipitate in the form of metal oxides and connect to the Cu-Co complex, coordinate to form a stable structure, and the further growth of the crystal will rely on the edge structure to grow in a specific direction, thereby producing different morphologies.

[0173] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a morphology-controlled Cu-Co composite metal catalyst, characterized in that: The following steps are involved: Dissolving copper salt and cobalt salt in an organic solvent to obtain a metal salt solution; dissolving the nitrogen-containing compound in an organic solvent to obtain a nitrogen-containing compound solution; adding the nitrogen-containing compound solution to the metal salt solution to carry out a hydrothermal reaction to obtain a catalyst precursor; calcining the calcined material to obtain the Cu-Co composite metal catalyst; The calcined material is a catalyst precursor or a catalyst precursor-cerium compound mixture; The temperature of the hydrothermal reaction is 100-200°C; The temperature of the hydrothermal reaction is greater than or equal to 100° C. and less than or equal to 120° C., and when the calcined material is a catalyst precursor, the Cu-Co composite metal catalyst has a sea urchin-like morphology; The temperature of the hydrothermal reaction is greater than 120° C. and less than or equal to 160° C., and when the calcined material is a catalyst precursor, the morphology of the Cu-Co composite metal catalyst is petal-shaped; When the temperature of the hydrothermal reaction is greater than 160° C. and less than or equal to 200° C., and when the calcined material is a catalyst precursor, the Cu-Co composite metal catalyst has a flaky morphology; When the temperature of the hydrothermal reaction is 100-200° C. and the calcined material is a catalyst precursor-cerium compound mixture, the Cu-Co composite metal catalyst has a flaky morphology; and the mass ratio of the catalyst precursor to the cerium compound in the catalyst precursor-cerium compound mixture is 1:0.3-1, calculated as oxides.

2. The preparation method according to claim 1, characterized in that: The copper salt includes one or more of copper nitrate, copper sulfate, copper chloride and copper acetate, the cobalt salt includes one or more of cobalt nitrate, cobalt sulfate, cobalt chloride and cobalt acetate, the organic solvent includes one or more of N,N-dimethylamide, methanol, ethanol and acetone, and the nitrogen-containing compound includes one or more of ammonium chloride, ammonium carbonate, ammonium bicarbonate and urea.

3. The preparation method according to claim 1, characterized in that: The copper salt is calculated as copper oxide, the cobalt salt is calculated as cobalt oxide, and the mass ratio of the copper salt to the cobalt salt is 1 to 5:1; in the metal salt solution, the total mass of the copper salt and the cobalt salt and the amount of the organic solvent are 0.05 to 0.2 g / mL; In the nitrogen-containing compound solution, the mass ratio of the nitrogen-containing compound to the organic solvent is 0.01-0.05:

1.

4. The preparation method according to claim 1 or 3, characterized in that: The volume ratio of the metal salt solution to the nitrogen-containing compound solution is 1:0.2-1.

5. The preparation method according to claim 1, characterized in that: The nitrogen-containing compound solution is added dropwise at a rate of 0.5 to 2 mL / min; After the nitrogen-containing compound solution is added, constant temperature stirring and ultrasound are sequentially performed, wherein the constant temperature stirring temperature is 30 to 50° C. and the time is 2 to 6 hours; The power of the ultrasound is 50-100KW, the frequency is 40-80KHz, and the time is 0.5-5h.

6. The preparation method according to claim 1, characterized in that: The hydrothermal reaction time is 6 to 24 hours.

7. The preparation method according to claim 1 or 6, characterized in that: After the hydrothermal reaction, the method further comprises: washing and drying the obtained solid in sequence to obtain the catalyst precursor, wherein the drying temperature is 60 to 150° C. and the drying time is 12 to 24 hours.

8. The preparation method according to claim 1, characterized in that: The calcination is carried out in a reducing atmosphere, the reducing atmosphere comprises a reducing gas and a balance gas, the volume concentration of the reducing gas in the reducing atmosphere is 10% to 50%, the reducing gas comprises H2, CO or NO; the air intake flow rate of the reducing atmosphere is 100 to 200 mL / min; The calcination temperature is 500-800° C., the rate of heating to the calcination temperature is 1-5° C. / min, and the heat preservation time is 2-5 hours.

9. The Cu-Co composite metal catalyst obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the Cu-Co composite metal catalyst according to claim 9 in photoelectrocatalysis or CO purification.